Optimal Extraction and Spray-Drying Anthocyanin from Perilla Frutescens - Hoang, Thi Ngoc Nhon; Nguyen, Thi Que Tran; Nguyen, Minh Phuc; Tran, Thi Huyen Linh; Le, Thi Hong Anh (Engineering and Technology For Sustainable Development, 2024)
Perilla frutescens has been commonly used as a food ingredient and in folk medicine. Anthocyanins, with many biological activities, have potential applications in food and pharmaceuticals. This study aimed to determine the optimal conditions for anthocyanin extraction with solvents before investigating the effects of spray drying conditions to obtain anthocyanin powder. The result shows that 72% ethanol at 63 ℃ in 90 min resulted in the optimal anthocyanin content of 3.373 mg/g DM. The suitable conditions for spray-drying to obtain anthocyanin powder were at 160°C with an input flow rate of 7 mL/min and a carrier agent concentration of 25%. A scanning electron microscope (SEM), X-ray radiation (XRD), and Fourier-transform infrared spectroscopy (FT-IR) confirmed effective microencapsulation, providing a basis for further research and applications of anthocyanin powder from this material.